Factors affecting rice farm in Bangladesh: A stochastic frontier approach - Ferdushi, Kanis Fatama; Kamil, Anton Abdulbasah; Mustafa, Adli; Baten, Md Azizul (AENSI Publisher), 2013)
The aim of this paper is to estimate of efficiency with Cobb-Douglas Stochastic Production Model (SFA) having time varying inefficiency effects model. The agricultural panel data were consider for this analysis during 1989-2008. The data were considered of Aus, Aman and Bororicefarm of Bangladesh with the combination of unpredictable environmental variable as rainfall, temperature and humidity.The model was categorized into two different types according to having ecological case or not.Categorization has been done to uncover a significance impact of environmental variable on rice.Second, to identify the source of efficiency by tobit analysis which are working behind the rice farm of Bangladesh. At last environmental effects has been identified to see the impact of environmental variable on rice production for Aus, Aman and Boro. Mean efficiency of rice farm in Bangladesh is .6497 and .6582 which have got through two different cases i.e. with and without environmental variable cases respectively .In case of without environmental variable the mean efficiency of Aus , Aman and Boro rice is .4543, .5336 and .9609 respectively. But efficiency of rice farm with environmental variable is bit less than efficiency without environmental variable. Most of the time environmental variable is a blessing for rice farm but sometimes it causes a great hamper which has been distinguished from these results.Tobit analysis also were carried for this paper to identify the significance of input variable and it has been shown that area, seed, fertilizer, rainfall, temperature and humidity is statistically significant variable on Aus, Aman and Boro rice.